The Seasons of a Ceo's Tenure - Hambrick, Donald C.; Fukutomi, Gregory D. S. (Academy of Management Review, 1991)
This article proposes a model of the dynamics of the CEO's tenure in office. The central argument is that there are discernible phases, or seasons, within an executive's tenure in a position, and that these seasons give rise to distinct patterns of executive attention, behavior, and, ultimately, organizational performance. The five delineated seasons are (a) response to mandate, (b) experimentation, (c) selection of an enduring theme, (d) convergence, and (e) dysfunction. The theoretical and practical implications of the model are discussed.